Effect of fibrinogen concentration and platelet count on the inhibitory effect of abciximab and tirofiban - Renda, Giulia; Rocca, Bianca; Crocchiolo, Roberto; De Cristofaro, Raimondo; Landolfi, Raffaele (Thrombosis and Haemostasis, 2003)
Glycoprotein (Gp) IIb/IIIa blockers are powerful antithrombotic agents, but display a wide variability of their effect using weight-adjusted dosing. We investigated whether some hemostatic variables affected in vitro platelet inhibition exerted by the antibody abciximab and the peptidomimetic tirofiban. High fibrinogen concentrations reduced platelet inhibition by tirofiban, assessed in whole blood (r = –0.85, n = 10, p <0.01) and in platelet rich plasma (r = –0.89, n = 10, p <0.01) through PFA 100 and Born’s aggregometry assay, respectively. Both drugs were unaffected by von Willebrand factor levels, while platelet count was inversely related to their inhibitory effect (tirofiban: r = –0.9, n = 7, p <0.01; abciximab: r = –0.81, n = 9, p <0.01). Analysis of GpIIb-IIIa blockade showed that receptor occupancy at a fixed abciximab dose was inversely related to platelet counts. These experimental data were in agreement with the classical model of receptor saturation by a tight binding inhibitor.A role for fibrinogen and/or platelet count in influencing the antithrombotic properties of platelet GpIIb-IIIa antagonists can be hypothesized.
Keywords: Platelet; GpIIb-IIIa blockers; fibrinogen; receptor occupancy; inhibition